Meningkatkan Kemampuan Motorik Halus Anak Melalui Belajar Sambil Bermain dengan Kegiatan Stempel Bunga di TK Darma Wanita Jelantik - Baiq Subayati (Jurnal Paedagogy, 2022)
The purpose of this study was to improve children's fine motor skills through learning while playing with flower-shaped stamping activities through the use of banana midrib media in Darma Wanita Jelantik Kindergarten. This study used a classroom action research method with the research subjects being group A2 with a total of 15 students. The data collection technique is by using observation sheets and documentation. While the data analysis technique is descriptive qualitative and quantitative analysis. The results of this study indicate that the physical ability of children's fine motor skills through learning while playing with flower-shaped stamping activities through the use of banana midrib media in Darma Wanita Jelantik Kindergarten has increased. This is evident from the data in the first cycle of 47% increased to 87% in the second cycle, and those that began to develop in the first cycle were 33% decreased to 13% in the second cycle.